DEVELOPMENT OF PROJECT BASED BLENDED LEARNING (PjB2L) MODEL TO INCREASE PRE-SERVICE PRIMARY TEACHER CREATIVITY - Wahyudi Wahyudi; Adi Winanto (Universitas Pendidikan Ganesha, 2018)
This research aims to develop project based blended learning model to grow pre-service primary teacher students’ creativity in designing lesson plan. This research was conducted due to the increasing needs in the 21st century. The method used in this research was R&D with ASSURE development model consisting of six stages. Product validation was done through an expert’s assessment by using the expert’s validation sheet. Product effectiveness was seen by implementing limited development testing to a particular class with a one group pretest-posttest design and the result was analyzed by using a Paired-Samples T-Test. The result of this research was in the form of a creative learning model based on project-based learning and blended learning to increase the creativity of pre-service primary teacher college students in designing a lesson plan. Validity of the learning model was proven by the result of the expert assessment in learning (face-to-face and on-line), material and instructional media. Effectiveness of the learning model was also proven on the basis of Paired-Samples T-Test of students’ pretest and posttest.